Mafhum Al-Matsal As-Sa’ir wa Khashaishihi wa ma Yusyabihuhu min Al-Mushthalahat ‘Inda Al-‘Arab - Jumahalaso, Salih Muhammad (el Harakah: Jurnal Budaya Islam, 2020)
تتركز هذه المقالة على تحديد مفهوم الكلمة «المثل» ومشتقاتها المختلفة في المعاجم العربية وفي التعبيرات القرآنية، وتمعن النظر فيما للكلمة من المدلولات المتباينة كالمثل الخرافي/الفرضي، والمثل القرآني والمثل السائر، وتدرس بصفة خاصة مفهوم «المثل السائر» وما يشابهه من العبارات العربية والمصطلحات الأدبية والبلاغية كالحكمة والتشبيه والمجاز وغيره، وذلك لبيان ما بين المثل السائر وبين هذه المصطلحات من الائتلاف والاختلاف، وأهم خصائص المثل السائر وأسرار استعماله مما تتناول المقالة، وذلك لكسب المفهوم الصحيح للمثل السائر ولزيادة الاهتمام به ودراسته. ومما توصلت إليها المقالة من النتائج أن إطلاق اللفظة «المثل» مجردا لا تظهر المقصود منها إلا بإضافة صفة إليها فيقال المثل الفرضي أو المثل السائر، وأنه لا يسمى مثلا سائرا إلا ما يكون سائرا بين الناس من التعبير، وأن المثل السائر يستعمل لتشبيه بين حالين: «المورد والمضرب». وقد نسج الباحث في جمع المعلومات وتحليلها على منوال المنهج الوصفي التحليلي كما استعان بالاستبانات المعبئة الالكترونية والورقية. وأخيرا اختمت المقالة بعدد من الاقتراحات والتوصيات التي تمت الصلة بفهوم المثل واسستعمالاته. This paper focuses on explaining the concept of the Arabic word “almatsal” and it’s various derivatives in the Arabic lexicology and Qur’anic expressions.It equally explains different usage of the word (Almathal) as Almatha alkhurafi (legendary proverb) almathal alQur’ani (Quranic proverb) etc. The paper particularly concentrates on what is known as “almatsal as-sair” (Common Proverb) and other related literary and rhetoric terms such as idiomatic/wisdom expression, simile, figure of speech etc, in order to distinguish and make clarification of similarities and dissimilarities among them, characteristics of the said proverb were also discussed. Some of the findings of the paper include: the term “almatsal” has several meanings and usage pending on adjective attached to it, alMathel as-sair can only be used for a common expression and that it is for comparing two different instances (almawrid: where the statement is made for the first time and almadrab: (where the statement is quoted). The researcher followed a descriptive analytical method, and administered both electronic and paper-based questionnaires. The article concluded with a number of suggestions and recommendations.